Coronary artery disease with heavily calcified lesions – literature review of novel therapeutic methods - Tomasz Furgoł; Karolina Karska; Michał Miciak; Joanna Jureczko; Konrad Gigoń; Marcin Jezierzański; Paweł Jureczko (Folia Medica)
Coronary artery disease and atherosclerosis are a very significant and widespread problem in modern medicine. The development of current diagnostics and treatment of atherosclerotic lesions is moving towards minimally invasive methods. The purpose of this article is to present selected novel methods of treating coronary atherosclerosis, comparing their effectiveness, indications, contraindications, and possible complications. A literature review of selected treatment methods for calcified atherosclerotic lesions was conducted in the online databases of PubMed, PubMed Central, Google Scholar, and NCBI. It includes original and review papers. The main language of the articles was English. The search used keywords such as “coronary artery disease,” “calcified atherosclerotic lesions,” “rotational atherectomy,” “intravascular lithotripsy,” and “RotaTripsy,” as well as related phrases. After analyzing the abstracts, the papers that most closely matched the stated topic were selected. Atherosclerosis is the leading cause of coronary heart disease incidence. Several risk factors, both non-modifiable and modifiable, predispose to its occurrence. Heavily calcified atherosclerotic plaques are associated with a higher risk of coronary artery disease consequences. Currently, methods such as CT coronary angiography and optical coherence tomography are used for diagnosis. Endovascular therapies are now recommended for the treatment of atherosclerosis with heavily calcified plaques. Rotational atherectomy, intravascular lithotripsy and RotaTripsy are promising methods for treating high-grade atherosclerosis with calcified deposits. However, especially in the case of RotaTripsy, further clinical studies are required to better evaluate the efficacy of this novel method.